Environmental stewardship for gold mining in tropical regions - A Isahak; S Surif; M Sahani; A Gill; J Phang (Journal of Degraded and Mining Lands Management, 2013)
Mining has gained strong popularity in recent years due to the increase in global demand for metals and other industrial raw material derived from the ground. However, information and good governance regarding activities related to mining is still very much lacking especially in underdeveloped and developing countries in the tropics. In Malaysia, the importance of environmental stewardship in mining is a new phenomenon. The new National Mineral Policy 2 calls for compliance with existing standards and guidelines, stresses on progressive and post mining rehabilitation as well as promotes the gathering and dissemination of information, best mining practices, public disclosure and corporate social responsibility. Our preliminary studies however have shown that its implementation may have been hampered by inadequate legal and administrative structures, lack of freedom of information, physical inaccessibility, lack of information and public participation. In this presentation, the above issues and measures to reduce the impact of mining, particularly that of gold on the environment with a special focus on Malaysia is discussed. These measures include alternative gold extraction methods, appropriate tailing dam construction and management, health risk assessment and risk management, compliance with the Cyanide Code and liberalization of access to information, facilitation of access to justice, the strengthening of legal and administrative structures as well as corporate accountability to the public as part of corporate social responsibility.